HUBUNGAN SPIRITUAL SUPPORT DENGAN TINGKAT KECEMASAN IBU HAMIL TRIMISTER III YANG TERDAMPAK ERUPSI GUNUNG MARAPI - Marisa Lia Anggraini; Rifdha Wahyuni (Ensiklopedia of Journal, 2026)
The anxiety experienced by pregnant women in disaster situations can have a significant impact on maternal health and fetal development. The purpose of this study was to determine the relationship between spiritual support and anxiety levels in third-trimester pregnant women affected by the eruption of Mount Marapai in the Lasi Community Health Center work area. This research wa an analytical study with a cross-sectional design. The population was all 44 third-trimester pregnant women. The sample was selected using the total population method. Primary data were collected using a questionnaire. The collected data were then processed manually and analyzed using a statistical program (SPSS). Data analysis included univariate analysis using frequency distribution and bivariate analysis using the chi-square test (p 0.05) to determine the relationship between variables. The univariate analysis showed that of the 44 respondents, 7 (15.9%) had long spiritual support, while 8 (18.5%) had high levels of anxiety. The bivariate analysis showed a relationship between spiritual support and anxiety levels in third-trimester pregnant women affected by the Mount Merapi eruption (p = 0.016). This study demonstrates the importance of spiritual support in preventing anxiety in pregnant women. Close family members are expected to provide maximum spiritual support to pregnant women to reduce anxiety during the Mount Merapi eruption. This study is expected to provide input for local community health centers and serve as a basis for further research.Keywords: Spiritual Support, Pregnant Women’s Anxiety, Mount Merapi Eruption